2006
DOI: 10.4049/jimmunol.177.1.557
|View full text |Cite
|
Sign up to set email alerts
|

Agonistic Monoclonal Antibody Against CD40 Receptor Decreases Lymphocyte Apoptosis and Improves Survival in Sepsis

Abstract: Sepsis causes a marked apoptosis-induced depletion of lymphocytes. The degree of lymphocyte apoptosis during sepsis strongly correlates with survival. CD40, a member of the TNFR family, is expressed on APCs and has potent antiapoptotic activity. In this study we determined whether an agonistic Ab against CD40 could protect lymphocytes from sepsis-induced apoptosis. Secondly, we examined potential antiapoptotic mechanisms of the putative protection. Lastly, we aimed to determine whether anti-CD40 treatment coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 54 publications
1
31
2
Order By: Relevance
“…In accordance with our results, Iwata et al reported that mice which were transgenic for Bcl-2 in their myeloid-derived cells had decreased sepsis-induced apoptosis in their intestinal epithelial cells [8]. The mechanism of this cross-protection is unknown but has been reported by other groups [5][6][7][8][9][10]. Iwata et al speculated, however, that the protective action of Bcl-2 over expressing cells was via a "trans" effect, i.e., Bcl-2 over expressing cells released an unknown cytoprotective factor which prevented death in non-Bcl-2 over expressing cells of distinct and distant lineages.…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations
“…In accordance with our results, Iwata et al reported that mice which were transgenic for Bcl-2 in their myeloid-derived cells had decreased sepsis-induced apoptosis in their intestinal epithelial cells [8]. The mechanism of this cross-protection is unknown but has been reported by other groups [5][6][7][8][9][10]. Iwata et al speculated, however, that the protective action of Bcl-2 over expressing cells was via a "trans" effect, i.e., Bcl-2 over expressing cells released an unknown cytoprotective factor which prevented death in non-Bcl-2 over expressing cells of distinct and distant lineages.…”
Section: Introductionsupporting
confidence: 81%
“…The cecal ligation and puncture (CLP) technique as developed by Chaudry et al [16] and modified by our laboratory was used to induce septic peritonitis as previously described [4][5][6][7]. In brief, mice were anesthetized and an abdominal incision was made.…”
Section: Induction Of Polymicrobial Sepsismentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to the inhibition of lymphocyte apoptosis, it has also been shown that activating CD40, a potent anti-apoptotic member of the TNF receptor family, provides extensive protection against sepsis-induced lymphocyte apoptosis and improves survival in sepsis by a mechanisms involving Bcl-xL [57]. The cell membrane permeable TAT-Bcl-X L peptide construct as well as a TAT-conjugated peptide of the anti-apoptotic BH4 domain of Bcl-X L (TAT-BH4) decreased sepsis-induced splenocyte T-and B-cell apoptosis to near sham levels in experimental murine sepsis.…”
Section: Inhibiting Apoptosis Improves Septic Survival -Therapeutic Omentioning
confidence: 99%